Legal Considerations of Marriage Dispensation Cases For Couples That Lead to Divorce - Zaidah, Yusna; Husna, Hatimul; Mubarak, Ahmad (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Dispensation of marriage by the court is an attempt to assess the suitability and readiness of couples who are not old enough to marry. However, it turns out that the couple who married under dispensation of marriage later divorced in the same court. This phenomenon shows that there are substantive problems in judicial practice that are interesting to research with the aim of examining the legal facts / reasons for determining marriage dispensation which then divorced in the same court. By using a normative legal method with a case approach, which is based on an analysis of a copy of the marriage dispensation determination and the Religious Court's divorce decision against the same couple as the primary legal material. The results showed that there were similarities in the legal considerations put forward by judges in several marriage dispensation decisions, which indicated the use of a pattern of case handling that tended to be uniform without considering the specific conditions of each case revealed in the posit. This led to a mismatch between the legal considerations and the concrete reality of the litigants. This finding shows the inconsistency and shallowness of juridical considerations, especially in determining the existence of very urgent reasons as the basis for the feasibility of granting marriage dispensation, which had an impact on the unsettled household of the young couple and led to the filing of a case that ended with the issuance of a divorce verdict. In fact, judges should be selective, based on benefit in assessing the reasons for filing a marriage dispensation application because this assessment is the last resort to maintain the continuity of the household, so that it does not lead to divorce.